The Analgesic Efficacy of Intra-Articular Acetaminophen in an Experimental Model of Carrageenan-Induced Arthritis - Oguzhan Arun; Ozgur Canbay; Nalan Celebi; Altan Sahin; Ali Konan; Pergin Atilla; Ulku Aypar (Pain Research and Management)
BACKGROUND: Acetaminophen is one of the most common drugs used for the treatment of pain and fever.